Monoclonal antibodies and reagents for botulinum research. (6th November 2012) - Stanker, Larry H.; Cheng, Luisa W.
Botulinum neurotoxin (BoNT) is produced by Clostridium botulinum as a dichain protein of ~ 150 kDa that blocks acetylcholine release resulting in muscular paralysis. Diagnosis of BoNT often relies on the mouse bioassay that has a detection limit of 10–20 pg/mL and can take up to four days to complete. Rapid in vitro methods for toxin detection are needed and to date, most rely on either immunoassay or endopeptidase activity. In the latter, many also use specific antibodies to concentrate the toxin. We have developed panels of monoclonal antibodies (mAbs) to purified toxin, serotypes A, B and E, as well as mAbs to the non-toxic associated proteins. Application of these mAbs in sandwich ELISAs and assay performance in milk and other foods is discussed. The assays described here are able to detect toxin in a few hours, at levels lower than the mouse bioassay.